Strategic management : - Hatten, Kenneth J. (George Mason University, 1987)
Integrates academic theory with business practices in strategic management. Illustrating concepts with examples from progressive global organizations, the text features application-oriented cases. It draws insight from business disciplines as well as disciplines from the social sciences.